Evaluation of Multi-Literacy Education Program at The Community Learning Activity Center in Palangka Raya City - Sardimi Sardimi; Ety Ariani; Aghnaita Aghnaita (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2022)
This is related to the quality of one's life so that it can open up public insight. The purpose of this study was to analyze the evaluation of the program on the aspects of context, input, process, and product of the multi-literacy education program at Learning Center (PKBM) Luthfillah, Palangka Raya. PKBM is an educational facility provided to provide non-formal education for citizens. Evaluation of the program that has been implemented uses the Context, Input, Process, and Product (CIPP) model by analyzing the components of the context, input, process, and product of the Multiliteracy Education program implemented. This research is a type of qualitative research. The research instruments used were observation, interviews, and documentation. The results of the research show: (1) in the context aspect, the program implemented has fulfilled the learning needs of the students, and the program objectives can be achieved as expected; (2) in the input aspect, educators and program organizers already have the expected competencies. It's just that for the initial abilities of students, the basic requirements for ownership of the Sukma have not been met; (3) in the process aspect, the learning strategies used are in accordance with the conditions of the students, namely andragogic, practical, and thematic strategies; (4) in the product aspect, students have graduated from the advanced literacy education program and have been able to apply the learning outcomes that have been obtained. However, the student's graduation certificate has not been received in the form of SUKMA-L.